2018
DOI: 10.1097/ccm.0000000000003227
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Evidence-Based Interventions in Patients with Acute Infections in a Resource-Limited Setting: A Before-and-After Feasibility Trial in Gitwe, Rwanda

Abstract: Our results indicate that a focused education program and implementation of an infection treatment bundle in clinical practice increased the rate of early evidence-based interventions in patients with acute infections (mostly malaria) admitted to a sub-Saharan African district hospital. Provision of material resources did not further increase this rate. While no safety issues were detected, this could be related to the very low disease severity of the enrolled patient population (www.clinicaltrials.gov: NCT026… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In this study, we externally validated the ability of the UVA score to predict in-hospital mortality in a cohort of patients with acute infection admitted to a hospital in Rwanda who were not part of the UVA score derivation cohort [ 7 ]. In doing so, despite a 10% difference in case fatality rates between the derivation and validation cohorts (17% vs 7%), we found that the AUC for the prediction of in-hospital mortality was identical between derivation and validation cohorts at 0.77 [ 7 , 9 ]. Increasing UVA scores were associated with increased case fatality rates and odds ratio of death.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In this study, we externally validated the ability of the UVA score to predict in-hospital mortality in a cohort of patients with acute infection admitted to a hospital in Rwanda who were not part of the UVA score derivation cohort [ 7 ]. In doing so, despite a 10% difference in case fatality rates between the derivation and validation cohorts (17% vs 7%), we found that the AUC for the prediction of in-hospital mortality was identical between derivation and validation cohorts at 0.77 [ 7 , 9 ]. Increasing UVA scores were associated with increased case fatality rates and odds ratio of death.…”
Section: Discussionmentioning
confidence: 93%
“…We performed a secondary analysis of data collected from adults ≥18 years admitted with an acute infectious disease to Gitwe District Hospital from the adult and pediatric Emergency Department of Gitwe District Hospital as well as eight referring health centers in the Ruhango District, Southern Province, Rwanda from March 2016 until March 2017 [ 9 ]. In the original study, using a data collection tool ( S1 Fig ), acute infection was defined as a suspected or confirmed infection, which was based on a clinical assessment and present for less than two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Given that improved critical care outcomes are possible outside of the ICU [19; 27, 28] and given the dearth of ICU physician presence in Haiti and other LMICs, ramping up critical care education and training for non-ICU clinicians and nurses is crucial. Structured critical care training can reduce adult [29] and pediatric ICU mortality in LMICs [3032].…”
Section: Discussionmentioning
confidence: 99%